Comparison of nerve conduction velocities of lower extremities between football players and controls - Aksu, E.; Colak, T.; Selekler, H. M.; Colak, E.; Mülayim, S.; Son, M.; Bamac, B.; Colak, S. (South African Journal for Research in Sport, Physical Education and Recreation, 2023)
This study aimed to compare neuronal function in the lower limbs of elite footballers and an age-matched control group. Conduction velocity, response latency and amplitude following electrical stimulation were investigated. Thirty male football players and 30 untrainedmales comprised the subject and control groups, respectively. We showed that professional football players have significantly slower sural nerve conduction velocity than untrained controls(p<0.05). Although we found no signs of neuropathy, mild changes in nerve conduction velocity were evident in the sural nerve of the players. Motor conduction velocity of tibial nerve was also significantly prolonged in this group when comparing dominant and non-dominant extremities (p<0.05).The tibial nerve muscle action potential amplitude was lower in the players` dominant limbs compared with the controls (p<0.05). We found no statistical difference in motor conduction velocities, distal latencies and amplitudes of the common peroneal nerve when comparing players and controls in both dominant and non-dominant limbs (p>0.05). Our results showed abnormalities of function in the sural and tibial nerves in football players compared with untrained controls, which may indicate early signs of neuropathy.